Los Pictogramas en el proceso de iniciación a la lectura de los niños y niñas de primer año de Educación Básica de la Unidad Educativa Comunitaria Intercultural Bilingüe “General Rumiñahui” de la Comunidad El Lirio, Cantón Colta, Provincia De Chimborazo. Periodo mayo – octubre 2021 - Chimbolema Gualli, Rosa Paulina (2022)
The objective of this research was to determine the importance of pictograms as a strategy in the process of initiation to the reading of children in the first year of Basic Education of Unidad Educativa Comunitaria Intercultural Bilingüe “General Rumiñahui,” El Lirio community, Colta canton, Chimborazo province, May - October 2021, understanding that the pictograms are a didactic strategy that benefits the development of the initiation of reading. Methodologically, the research has a non-experimental design of a transversal, primary, and field type; by the level, it was descriptive, by the analytical-synthetic method. The population was the nine students of the first year of primary education, its sampling was non-probabilistic and intentional, the technique was an observation, and the instrument was the observation sheet, through which the analysis of the results could be carried out, reaching several conclusions; that a correlation is established between the pictograms and the reading initiation process since the pictograms are considered as tools of linguistic communication, which intervenes in the reading process.